2006
DOI: 10.1256/qj.04.108
|View full text |Cite
|
Sign up to set email alerts
|

Formation and release of symmetric instability following Delta‐M adjustment

Abstract: SUMMARYConditional Symmetric Instability (CSI) and Delta-M adjustment have both been suggested as possible mechanisms to explain the slantwise circulations that lead to two-dimensional precipitation bands near midlatitude cold fronts. Previous work has shown how the initial state required for CSI to occur is similar to the state produced as a result of Delta-M adjustment. An idealized dry numerical model is used to test the hypothesis that slantwise circulations can occur due to the release of symmetric instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…This duality in the mechanisms leading to slantwise circulations was also found in the idealized dry twodimensional numerical-model simulations of Morcrette and Browning (2006). They found that small regions of symmetric instability formed below the M-adjustment updraught, and that a second updraught formed in the region where this instability was being released.…”
Section: Comparison With Other Idealized Studiessupporting
confidence: 58%
See 1 more Smart Citation
“…This duality in the mechanisms leading to slantwise circulations was also found in the idealized dry twodimensional numerical-model simulations of Morcrette and Browning (2006). They found that small regions of symmetric instability formed below the M-adjustment updraught, and that a second updraught formed in the region where this instability was being released.…”
Section: Comparison With Other Idealized Studiessupporting
confidence: 58%
“…The 861 model is run with 64 vertical levels; this gives a grid spacing of 200-300 m in the mid-troposphere, with higher resolution near the surface in the boundary layer. This horizontal resolution is coarser than the optimal resolution for resolving small-scale multiple slantwise circulations (according to Lean and Clark (2003) and Morcrette and Browning (2006)), but was chosen to make these large-domain simulations manageable. Morcrette and Browning (2006) found that simulations with 4 km horizontal grid boxes produced circulations similar to those obtained with finer resolutions, although they took longer to evolve.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In this model, the number of computational levels has been increased from 58 to 80, a nonorographic gravity wave drag based on Hines (1997a,b) has been implemented, and a new radiation scheme from Li and Barker (2005) using a correlated-k distribution for gaseous transmission is included. Other improvements to the model physics, related to the representation of deep convection [e.g., inclusion of the Bechtold et al (2001) scheme], of slantwise convection (see Ma 2000;Morcrette and Browning 2006), and of land surface processes (inclusion of the Canadian Land Surface Scheme, CLASS; Verseghy 1991; Verseghy et al 1993) are currently being explored.…”
Section: Discussionmentioning
confidence: 99%
“…M-adjustment was put in a chronological sequence with CI and SI by Morcrette and Browning (2006), hereafter referred to as MB, to form a consistent picture that accounts for the widespread simultaneous presence of those three forms of unstable motion in the atmosphere. Numerical experiments with an idealized version of an operational forecast model were performed by Gray and Dacre (2008) to reproduce the hypothesized sequence of events in an idealized environment.…”
Section: Introductionmentioning
confidence: 99%